2021
DOI: 10.3389/fped.2021.700748
|View full text |Cite
|
Sign up to set email alerts
|

Are the Growth Standards of the World Health Organization Valid for Spanish Children? The SONEV Study

Abstract: Background: The use of different growth tables to assess the population's nutritional status has given rise to a series of limitations arising from the lack of consensus and uniform methodological criteria. This leads to a disparity of results that prevent an accurate and reliable diagnosis of whether a child is overweight or obese.Objective: The purpose of this study was to develop growth references for weight, height, and body mass index for Eastern-Spanish children from 6 to 16 years of age.Methods: The fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Finally, in the study carried out by Pérez-Bermejo et al 57 in Spain, significant differences were found in BMI values according to age between the two sexes at some ages, for this reason, the authors argued that, if the WHO reference were used, the rate of overweight and obesity would be double that of national references.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Finally, in the study carried out by Pérez-Bermejo et al 57 in Spain, significant differences were found in BMI values according to age between the two sexes at some ages, for this reason, the authors argued that, if the WHO reference were used, the rate of overweight and obesity would be double that of national references.…”
Section: Resultsmentioning
confidence: 97%
“… Note : Being several authors of this work the same, the article 57 has not been valued. Abbreviations : Y, Yes; N, No; U, Unclear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Defining international cut-offs provides numerous advantages and it allows researchers to make comparisons with other BMI references [ 43 ]. However, the lack of uniformity in the methodological criteria to develop growth references for childhood BMI could sometimes lead to disparity in the results [ 44 ]. For instance, the World Health Organization’s (WHO) BMI references values might not me suitable for all European children [ 44 ].…”
Section: Obesity and Metabolic Syndrome: Definitions And Reference Va...mentioning
confidence: 99%
“…However, the lack of uniformity in the methodological criteria to develop growth references for childhood BMI could sometimes lead to disparity in the results [ 44 ]. For instance, the World Health Organization’s (WHO) BMI references values might not me suitable for all European children [ 44 ]. Other BMI thresholds have been proposed by the U.S. Centers for Disease Control and Prevention (CDC), although the differences in the predictive capacity between the CDC reference and the World Obesity Federation’s reference are minimal [ 45 ].…”
Section: Obesity and Metabolic Syndrome: Definitions And Reference Va...mentioning
confidence: 99%